Flexible nonfullerene organic solar cells based on embedded silver nanowires with an efficiency up to 11.6%. Issue 5 (15th January 2019) - Dong, Xinyun; Shi, Pei; Sun, Lulu; Li, Jing; Qin, Fei; Xiong, Sixing; Liu, Tiefeng; Jiang, Xueshi; Zhou, Yinhua
Abstract : Flexible non-fullerene organic solar cells based on AgNWs embedded in polyimide substrates demonstrate a high efficiency up to 11.6%. Abstract : Light weight and excellent mechanical flexibility are the most important advantages of organic solar cells (OSCs), compared with their inorganic counterparts. However, the development of flexible OSCs lags behind the cells fabricated on rigid glass. Herein, we report efficient flexible nonfullerene OSCs with a novel device structure: AgNWs@PI/ZnO/active layer/MoO3 /Ag, where AgNWs@PI (silver nanowires embedded in polyimide substrates) is used as the substrate and the bottom electrode. Optimized ZnO processed from isopropyl alcohol (IPA) solutions physically does not destroy/dissolve the PI substrates, and is chemically compatible with the nonfullerene active layer. With PBDB-T-2F:IT-4F as the nonfullerene active layer, the fabricated flexible solar cell displays a power conversion efficiency of 11.6% ( V OC = 0.82 V, J SC = 19.6 mA cm −2, and FF = 0.72).